2015
DOI: 10.1016/j.mrgentox.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The methylating agent streptozotocin induces persistent telomere dysfunction in mammalian cells

Abstract: We analyzed chromosomal aberrations involving telomeres in the progeny of mammalian cells exposed to the methylating agent and antineoplastic/diabetogenic drug streptozotocin (STZ), to test whether it induces long-term telomere instability (by chromosome end loss and/or telomere dysfunction). Rat cells (ADIPO-P2 cell line, derived from Sprague-Dawley rat adipose cells) were treated with a single concentration of STZ (2mM). Chromosomal aberrations were analyzed 18h, 10 days, and 15 days after treatment, using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In addition, our experiments with rat cells exposed to STZ showed that this compound also induces long-term telomere instability in the form of incomplete chromosome elements, as previously observed in the short-term in Chinese hamster cells [57]. We found that STZ induces a transient increase in telomere length in ADIPO-P2 cells at 10 days after treatment, a delayed effect not related with telomerase activity, which remained unchanged in both treated and untreated cells [62]. Therefore, the persistence of chromosomal aberrations related to telomere dysfunction in rat cells exposed to STZ seems to be unrelated to telomerase activity or telomere length.…”
Section: Bleomycin (Blm) Streptonigrin (Sn) and Streptozotocin (Stz)supporting
confidence: 85%
See 1 more Smart Citation
“…In addition, our experiments with rat cells exposed to STZ showed that this compound also induces long-term telomere instability in the form of incomplete chromosome elements, as previously observed in the short-term in Chinese hamster cells [57]. We found that STZ induces a transient increase in telomere length in ADIPO-P2 cells at 10 days after treatment, a delayed effect not related with telomerase activity, which remained unchanged in both treated and untreated cells [62]. Therefore, the persistence of chromosomal aberrations related to telomere dysfunction in rat cells exposed to STZ seems to be unrelated to telomerase activity or telomere length.…”
Section: Bleomycin (Blm) Streptonigrin (Sn) and Streptozotocin (Stz)supporting
confidence: 85%
“…Finally, we found that also STZ induces persistent telomere dysfunction in rat cells, cytogenetically detected mainly as telomere FISH signal loss and duplications, most of them being chromatid-type aberrations [62]. We observed that STZ induces significantly more signal loss than duplications, telomere loss thus being the most significant effect of STZ on telomere function at the chromosome level in ADIPO-P2 cells.…”
Section: Bleomycin (Blm) Streptonigrin (Sn) and Streptozotocin (Stz)mentioning
confidence: 62%
“…injections (Reaven and Ho, 1991 ; Wang and Gleichmann, 1998 ; Yuan et al, 2016 ). STZ treatment causes typical aging-associated changes, such as telomere instability (Paviolo et al, 2015 ), mitochondrial dysfunction (Raza and John, 2012 ), genomic instability (Attia et al, 2009 ), metabolic dysfunction (Rodríguez-Mañas et al, 2009 ) and cellular senescence (Oubaha et al, 2016 ). Furthermore, T2DM induced by STZ i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning streptozotocin, we found that it also has a variable effect on telomere length in the long-term, since this drug had no significant effect at 18 h and 15 days after treatment, but induced telomere elongation at 10 days after treatment. These effects were not related with telomerase activity, which remained unchanged in both treated and untreated cells from 18 h to 15 days after treatment [36] . Therefore, the persistence of chromosomal aberrations related to telomere dysfunction observed in rat cells exposed to streptozotocin seems to be unrelated to telomerase activity or telomere length.…”
Section: Bleomycin Streptonigrin and Streptozotocinmentioning
confidence: 77%
“…The effect of these drugs on telomere length in hamster cells was not determined. More recently, we investigated the long-term effect (i.e., up to 15 days after treatment) of bleomycin, streptonigrin and streptozotocin on telomeres of rat cells (the ADIPO-P2 cell line, derived from dedifferentiated adipose cells from Spragüe-Dawley rats) [34][35][36] . Bleomycin and streptonigrin had a variable effect on telomere length, since they both induced telomere shortening at 18 h, telomere elongation at 10 days, and had no effect on telomere length at 15 days after treatment (Paviolo, unpublished).…”
Section: Bleomycin Streptonigrin and Streptozotocinmentioning
confidence: 99%